Corrigendum: A promoter toolbox for tissue-specific expression supporting translational research in cassava (Manihot esculenta)(Front. Plant Sci., (2022), 13, (1042379), 10.3389/fpls.2022.1042379) - Zierer, Wolfgang; Anjanappa, Ravi Bodampalli; Lamm, Christian; Chang, Shu Heng; Gruissem, Wilhelm; Sonnewald, Uwe (Frontiers in Plant Science, 2024)
In the published article, there was an error in the legend for Figure 2 and the legend for Figure S2 as published. In the Figure 2 legend, subfigure F2 – F6 were falsely labeled subfigure H2 – H6. In the Figure S2 legend, the subfigures C-F were incorrectly labeled and the labeling for subfigures G-H was missing. The corrected legend appears below. FIGURE 2 Representative GUS staining pattern of at least three events from pAtCAB1, pStLS1, pAtRBCS3B, pMeGBSS1, pStSSS3, and pStSTP1 promoter-reporter plants. pAtCAB1::GUS = A1) Source leaf (Inlay = Close-up), B1) Sink leaf, C1) Emerging leaves, D1) Petiole cross-section, E1) Upper stem cross-section, F1) Lower stem cross-section, G1) Storage root cross-section, H1) Fibrous roots, I1) GUS expression levels of four pAtCAB1::GUS lines relative to three pCaMV35S::GUS lines in %. pStLS1::GUS = A2) Source leaf, B2) Sink leaf, C2) Petiole cross-section, D2) Upper stem cross-section, E2) Storage root cross-section, F2) Fibrous roots. pAtRBCS3B::GUS = A3) Source leaf, B3) Sink leaf, C3) Petiole cross-section, D3) Upper stem cross-section, E3) Storage root cross-section, F3) Fibrous roots. pMeGBSS1::GUS = A4) Source leaf, B4) Sink leaf, C4) Petiole cross-section, D4) Upper stem cross-section, E4) Storage root cross-section, F4) Fibrous roots. pStSSS3::GUS = A5) Source leaf, B5) Sink leaf, C5) Petiole cross-section, D5) Upper stem cross-section, E5) Storage root cross-section, F5) Fibrous roots. pStSTP1::GUS = A6) Source leaf, B6) Sink leaf, C6) Petiole cross-section, D6) Upper stem cross-section, E6) Storage root cross-section, F6) Fibrous roots. Plants were either grown on the field at NCHU experimental station Taichung, Taiwan or in a greenhouse in Erlangen, Germany. Tissues from approximately 3-month-old cassava plants were used. FIGURE S2 Representative GUS staining pattern of three pCaMV35S::GUS promoter-reporter lines. A) Source leaf, B) Sink leaf, C) Emerging leaves, D) Petiole cross-section, E) Upper stem cross-section, F) Lower stem cross-section, G) Storage root cross-section, H) Fibrous roots. The authors apologize for these errors and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2024-05-24
Keywords: biotechnology; cassava; parenchyma; phloem; promoter; storage root; tissue; xylem